Auto-transplantation of teeth: Our Experience - Singh, Ashutosh Kumar; Shrestha, Lipika (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: To evaluate success rate of auto-transplantation of teeth with immature and mature root apex. Materials & Methods: Fifteen consecutively auto-transplanted teeth ( six with immature apex and nine with mature apex ) were followed up for a mean duration of 8.6 months and assessed for post transplant mobility, root resorption, root growth and pain. The transplanted teeth were assessed clinically and Intraoral periapical radiographs (IOPAR) were taken every three months. Results: Overall success rate was 73.3%. Higher success rate was observed for teeth with immature apex as compared to teeth with mature apex. Conclusion: Auto-transplantation can be used as reliable method for replacement of missing teeth if proper case selection and surgical protocol is followed.